Telemedicine And Artificial Intelligence, Early Detection And Prevention Of New Diseases In Prophylaxis Medicine (Progress Annals: Journal of Progressive Research, 2025)
Developments in the field of telemedicine and artificial intelligence play an important role in the early detection and prevention of new diseases in modern medicine. This article covers the main aspects of telemedicine, the use of artificial intelligence in diagnostics and their impact on preventive medicine based on scientific sources